Modern Formal Methods and Applications - Gabbar, Hossam A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Formal methods are a robust approach for problem solving. It is based on logic and algebraic methods where problems can be formulated in a way that can help to find an appropriate solution. This book shows the basic concepts of formal methods and highlights modern modifications and enhancements to provide a more robust and efficient problem solving tool. Applications are presented from different disciplines such as engineering where the operation of chemical plants is synthesized using formal methods. Computational biology becomes easier and systematic using formal methods. Also, hardware compilation and systems can be managed using formal methods. This book will be helpful for both beginners and experts to get insights and experience on modern formal methods by viewing real applications from different domains.
Fundamentals of Formal Methods -- Formal Methods for Process Systems Engineering -- Formal Methods for Production Chain Management -- Formalizing Waste Management -- Formal Methods for Modeling Biological Regulatory Networks -- Formal Methods for Specifying and Analyzing Complex Software Systems -- An Algebraic Approach to Hardware Compilation -- Formal Methods for UML.
Keywords: CHEMISTRY; CHEMISTRY -- MATHEMATICS; LOGIC DESIGN; COMPUTER SCIENCE; ENGINEERING MATHEMATICS; CHEMISTRY; MATH. APPLICATIONS IN CHEMISTRY; LOGICS AND MEANINGS OF PROGRAMS; MATHEMATICAL LOGIC AND FORMAL LANGUAGES; MODELS AND PRINCIPLES; COMPUTATIONAL SCIENCE AND ENGINEERING; APPL.MATHEMATICS/COMPUTATIONAL METHODS OF ENGINEERING